Liberty's last stand [compact disc, unabridged] - Coonts, Stephen, 1946- (Brilliance Audio, 2016)
Jake Grafton and Tommy Carmellini suddenly find themselves on the wrong side of the law when a public act of violence throws the country into chaos just before a presidential election. After martial law is declared and rioting begins, Grafton and Carmellini must risk everything to unravel a massive conspiracy and help a new resistance movement rise up against an unimaginable enemy.